An exploration of gender differences in the relationship between work family conflict and gambling problems. Issue 1 (2nd January 2016) - van der Maas, Mark
Abstract: The current study is an examination of gender differences in the experience of problems as a result of gambling. Using the framework of work–family conflict, this study compares men and women in terms of how their participation in work and family life relates to gambling problems as measured by the Problem Gambling Severity Index. Data from the 2008 Canadian Community Health Survey, a large representative sample of 28, 687 participants in three Canadian provinces, is analysed with generalized linear modeling. The findings of this study show that simultaneously occupying the roles of married spouse and working spouse is associated with more gambling-related problems for women, but fewer for men. The study concludes with a discussion of how the intersection of problem gambling and important aspects of social life presents different problems for men and women due to gendered expectations surrounding work and family life. Implications for the findings in relation to trends of increased use of electronic gaming machines by gambling providers are also discussed.